1999
DOI: 10.1177/108056999906200205
|View full text |Cite
|
Sign up to set email alerts
|

Using Practitioners' Viewpoints to Improve Accounting Students' Communications Skills

Abstract: The accounting profession has recognized the importance of emphasizing written and oral communications skills in the accounting curriculum. Innovations in tech nology have greatly enhanced educators' abilities to incorporate instruction in such skills. A survey of practitioners indicates strong agreement with the new writing requirements of the CPA exam. In addition, they endorse the use of information technology in preparing documents based on specific models and prescribed criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In addition, the quality of permanence that characterizes written work makes effective composition even more urgent as errors left unchecked in their letters or reports may cause dire effects such as miscommunication and devaluation of the audit firm's image and credibility. This assertion on the importance of writing in the accounting profession is supported by Nellermoe et al (1999) who confirmed that "typical accounting professionals would spend more time writing during the typical business day" (p. 50). Similarly, professionals from top public accounting firms in America who participated in the survey of Stowers and White (1999) ranked writing skills as significantly higher in importance than other communication skills.…”
Section: Composementioning
confidence: 87%
“…In addition, the quality of permanence that characterizes written work makes effective composition even more urgent as errors left unchecked in their letters or reports may cause dire effects such as miscommunication and devaluation of the audit firm's image and credibility. This assertion on the importance of writing in the accounting profession is supported by Nellermoe et al (1999) who confirmed that "typical accounting professionals would spend more time writing during the typical business day" (p. 50). Similarly, professionals from top public accounting firms in America who participated in the survey of Stowers and White (1999) ranked writing skills as significantly higher in importance than other communication skills.…”
Section: Composementioning
confidence: 87%
“…Among the essential writing skills, they discuss ways to reduce wordiness, convert passive to active voice, and correctly punctuate sentences. Corman (1986), Ingram and Frazier (1980) and Nellermoe et al (1999) identify wordiness as a particularly frequent and troublesome problem among accountants. In a survey of experienced accountants, Nelson et al (1996) found that wordiness and the passive voice often plague documents written by new-hires.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Business schools have been criticized for not adequately teaching the communication skills and competencies needed in today's serviceoriented, team-oriented, and decentralized environment (Maupin, 1993;Nellermoe, Weirich, & Reinstein, 1999;Pincus, Rayfield, & Ohl, 1994). Maes et al (1997) noted that the five classical management functions of planning, organizing, commanding, controlling, and coordinating, as developed by Fayol (1949), continue to be the managerial skills emphasized in business textbooks.…”
Section: Literature Reviewmentioning
confidence: 99%